Α1D‐Adrenoceptors are responsible for the high sensitivity and the slow time‐course of noradrenaline‐mediated contraction in conductance arteries. Issue 1 (28th August 2013) - Flacco, Nicla; Parés, Jaime; Serna, Eva; Segura, Vanessa; Vicente, Diana; Pérez‐Aso, Miguel; Noguera, María Antonia; Ivorra, María Dolores; McGrath, John C.; D'Ocon, Pilar
Abstract The objective of this study was to determine whether the different time‐course characteristics of α1‐adrenoceptor‐mediated contraction in arteries can be related to the subtypes involved. Contractile responses to noradrenaline (NA) were compared with inositol phosphate accumulation and extracellular signal‐regulated kinase (ERK)1/2 phosphorylation after α1‐agonist stimuli in the same vessels in the presence or absence of α1‐antagonists in rat or in α1‐subtype knockout (KO) mice. Aorta, where α1D‐AR is the main functional subtype, had higher sensitivity to NA (in respect of inositol phosphate [IP], pERK1/2, and contractile response) than tail artery, where the α1A‐adrenoceptor subtype is predominant. Furthermore, the contraction in aorta exhibited a slower decay after agonist removal and this was consistent in all strains harboring α1D‐adrenoceptors (from rat, α1B‐KO, and wild‐type [WT] mice) but was not observed in the absence of the α1D‐adrenoceptor signal (α1D‐adrenoceptor blocked rat aorta or aorta from α1D‐KO). IP formation paralleled α1‐adrenoceptor‐mediated contraction (agonist present or postagonist) in aorta and tail artery. High sensitivity to agonist and persistence of response after agonist removal is a property of α1D‐adrenoceptors. Therefore, the preponderance of this subtype in noninnervated conductance arteries such as aorta allows responsiveness to circulating catecholamines and prevents abrupt changes in vessel caliber when the stimulus fluctuates. Conversely, in innervated distributing arteries, high local concentrations of NA are required to activate α1A‐adrenoceptors for a response that is rapid but short lived allowing fine adjustment of the contractile tone by perivascular sympathetic nerves.